Synthesis and characterization of polyaminals from melamine derivative for carbon dioxide capture studies. (2021) - Senthilkumaran, M.; Saravanan, C.; Muthu Mareeswaran, P.
Abstract: Polyaminal network has rich CO2 -philic groups such as primary amine and triazine groups. Two types of polyaminals are synthesized using benzoguanamine with benzaldehyde (PPA-1) and terephthalaldehyde (PPA-2). The aminal formation is confirmed by FT-IR. Amorphous and sponge like structures of the polymers are studied by XRD and SEM analysis respectively. N2 sorption experiment is used to study the surface area and to calculate the pore volume.